Effects of exogenous selenium application on nutritional quality and metabolomic characteristics of mung bean (Vigna radiata L.) - Wang, Kexin; Yuan, Yuhao; Luo, Xinyu; Shen, Zhaoyang; Huang, Yinghui; Zhou, Haolu; Gao, Xiaoli (Frontiers in Plant Science, 2022)
Selenium (Se) biofortification is an important strategy for reducing hidden hunger by increasing the nutritional quality of crops. However, there is limited metabolomic information on the nutritional quality of Se-enriched mung beans. In this study, physiological assays and LC-MS/MS based widely targeted metabolomics approach was employed to reveal the Se biofortification potential of mung bean by evaluating the effect of Se on mung bean nutraceutical compounds and their qualitative parameters. Physiological data showed that foliar application of 30 g ha-1 sodium selenite (Na2SeO3) at key growth stages significantly increased the content of Se, protein, fat, total phenols, and total flavonoids in two mung bean varieties. widely targeted metabolomics identified 1080 metabolites, among which L-Alanyl-L-leucine, 9,10-Dihydroxy-12,13-epoxyoctadecanoic acid, and 1-caffeoylquinic acid could serve as biomarkers for identifying highly nutritious mung bean varieties. Pathway enrichment analysis revealed that the metabolic pathways of different metabolites were different in the Se enriched mung bean. Specifically, P1 was mainly enriched in the linoleic acid metabolic pathway, while P2 was mainly enriched in the phosphonate and phosphinate metabolic pathways. Overall, taken together, these results revealed the specific Se enrichment mechanism of different mung bean varieties. This study provides new insights into the comprehensive improvement of nutritional quality of mung beans.